(untitled) (Research, Society and Development, 2021)
The present study aimed to review the literature on the incorporation of substances to improve the mechanical, chemical and optical properties of composites. For this purpose, a search was performed in the PubMed database, using the descriptor "Composite Resins" combined through the Boolean operator AND with each of the following descriptors "Anti-bacterial Agents", "Bulk Fill", "Fillers" and "Photoinitiators ”. Eleven articles in English were selected. There are resins incorporated by bioglass (BV) that reduces the penetration of biofilm in marginal spaces of composites. Studies have shown that the integration of methacrylates and nanoparticles of amorphous calcium phosphate (NACP) favored the antibacterial action, as well as remineralization. Another author, supported the development of a self-repairing dental composite, as well as the incorporation of dimethylaminohexadecyl quaternary ammonium methacrylate (DMAHDM) that reduced the growth of biofilm without compromising its mechanical properties. Thus, there is a positive and effective evolution of resin composites, favoring improvements in physical and chemical properties. However, there is no unanimity as to which composite guarantees to eliminate all limitations.